MORPHOLOGY AND BIOLOGICAL FEATURES OF AGROTIS OBESA BOISDUVAL, 1829 (LEPIDOPTERA: NOCTUIDAE) (Scientific journal of the Fergana State University, 2024)
The article presents the distribution, morphological description and biology of Agrotis obesa. In terms of food specialization, it is a narrow polyphagm and belongs to the mesophilic ecological group; in terms of the seasonal aspect, it is a spring-summer-autumn species. One of the most common species, widespread in most anthropogenic landscapes.